(untitled) (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: Bacterial pneumonia is one of the most common causes of mortality and morbidity worldwide especially in adults. Objective: The purpose of this present study was to identify the aetiological agents and antimicrobial sensitivity pattern of bacterial pneumonia in patients admitted at intensive care unit (ICU). Methodology: This cross sectional study was carried out in the Department of Microbiology & Immunology at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh from August 2012 to July 2013. Blood and tracheal aspirates (TA) culture were done in clinically diagnosed pneumonia patients admitted in the ICU of BSMMU. PCR of TA was performed to identify Legionella species. Urine ICT of patients was done to detect Streptococcus pneumoniae and Legionella pneumophila serogroup 1 antigens. Antimicrobial susceptibility of isolated bacteria was done by disc diffusion method. Result: A total of 36 pneumonia patients admitted at ICU were recruited. The most common identified bacteria were Acinetobacter species (33.3%) followed by Pseudomonas species (30.5%), Klebsiella pneumoniae (11.1%), Escherichia coli (5.5%), Enterobacter aerogenes (5.5%), Legionella (8.3%), Citrobacterfreundii (2.8%) and Proteus mirabilis (2.8%). Majority of the bacteria were resistant to first line antibiotics and highly sensitive to carbapenems. Conclusion: Most common isolated bacteria are the Acinetobacter species, Pseudomonas species and Klebsiella pneumoniae among the pneumonic patients with the resistant to first line antibiotics and sensitive to carbapenems. J Shaheed Suhrawardy Med Coll, 2015; 7(1):22-25